2017
DOI: 10.1080/14764172.2017.1326609
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of 665 nm low level diode Laser Hat versus and a combination of 665 nm and 808nm low level diode Laser Scanner of hair growth in androgenic alopecia

Abstract: Results showed a statistically significant improvement in the laser scanner of the hair growth group compared with laser hat and the control group. The study showed that treatment with new laser devise had a promising result without any observable adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Apart from anecdotal evidence and non-controlled studies, LLLT showed superior hair growth-promoting effects in men and women with AGA compared to the sham-operating control group in eight randomized controlled clinical trials with the end point varying from 16 to 26 weeks. LLLT devices used in these studies include (1) 655-nm laser combs [11,12]; (2) a 635-nm and 655-nm laser comb [12]; (3) a helmet using 630-nm LED, 660-nm LED, and 650-nm laser [13]; (4) a helmet using 655-nm LED and 655-nm laser [14,15]; (5) a helmet using 660-nm LED and 650-nm laser [16]; (6) a 650nm laser dome fixed in a sport-style hat [17]; and (7) a 655-nm and 808-nm laser scanner [18]. A recent systematic review and network meta-analysis, evaluating the efficacy of nonsurgical treatments for AGA, indicated that LLLT is a highly effective treatment option for AGA; however, the quality of evidence is very low as determined by the risk of bias assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from anecdotal evidence and non-controlled studies, LLLT showed superior hair growth-promoting effects in men and women with AGA compared to the sham-operating control group in eight randomized controlled clinical trials with the end point varying from 16 to 26 weeks. LLLT devices used in these studies include (1) 655-nm laser combs [11,12]; (2) a 635-nm and 655-nm laser comb [12]; (3) a helmet using 630-nm LED, 660-nm LED, and 650-nm laser [13]; (4) a helmet using 655-nm LED and 655-nm laser [14,15]; (5) a helmet using 660-nm LED and 650-nm laser [16]; (6) a 650nm laser dome fixed in a sport-style hat [17]; and (7) a 655-nm and 808-nm laser scanner [18]. A recent systematic review and network meta-analysis, evaluating the efficacy of nonsurgical treatments for AGA, indicated that LLLT is a highly effective treatment option for AGA; however, the quality of evidence is very low as determined by the risk of bias assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Barikbin et al [23] described the use of the red light laser hat and the red light laser scanner for treating AGA and FPHL. In this randomized, double-blinded, controlled study, a total of 90 female and male patients were divided into 3 equal groups – Group 1: patients received 655 nm red light via laser hat ( n = 30); Group 2: patients received 655 nm red laser plus 808 nm infrared laser using a laser scanner of hair growth device ( n = 30); and Group 3: patients received no laser as the control group ( n = 30).…”
Section: Resultsmentioning
confidence: 99%
“…Eight out of the 10 studies used sham devices as controls. Of the 2 that did not use sham devices, minoxidil was used for one treatment group [25] and the other, no treatment was given to the control group [23].…”
Section: Discussionmentioning
confidence: 99%
“…). Seventy‐eight, met the inclusion criteria and were included in the quantitative analysis. A total of 15 888 participants (88.1% male) were included with an average age 36.0 ± 7.3 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two studies of the 78 included in the quantitative analysis had the data necessary for a network meta‐analysis. The included trials had 2421 randomized participants, which were 64.2% male.…”
Section: Resultsmentioning
confidence: 99%